PROBLEMATIKA PEMBUKTIAN DALAM TINDAK PIDANA MALPRAKTIK DOKTER DITINJAU DARI UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Syarifudin, Syarifudin (Justitia et Pax, 2024)
The malpractice is still far from the reach of criminal procedure. There are no specific regulations on malpractice and there are problems in proving criminal acts of malpractice so that this article uses the theory of evidence to provide legal certainty to fulfill the elements of error and criminal responsibility. This study uses a normative method to answer this problem so that the statute approach and case approach are used. The results of the study show that the problems in proving criminal acts of malpractice and the difficulty of collecting evidence (unus testis nullus testis) are obstacles to assisting the legal process, the complexity of proof in criminal law which is material and problematic in the legal vacuum space limited to the Criminal Code. Contextually, criminal responsibility for malpractice is not specifically regulated in the Criminal Code or medical malpractice, but after the enactment of Law 17 of 2023 concerning Health, it provides hope in protection and helps victims in seeking justice even though cases reported by victims are often in SP3 (Investigation Termination Order).